GAMBARAN PELAKSANAAN DIET DIABETES DENGAN PENERAPAN APLIKASI DM-DOS - Alwari, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Diabetes mellitus (DM) is a disease caused by an increase in blood sugar levels, one of the factors for an increase in blood sugar levels is due to a bad diet. Efforts to control blood sugar levels for DM sufferers can be done by providing health education in the form of implementing a good diet for DM sufferers using Android-based electronic media, namely diet settings on the DM-DOS application. Purpose: This study aims to find out the description of the Implementation of the Diabetes Diet with the Application of DM-DOS Method: This research uses a quantitative research method with a simple descriptive research design that aims to see a description of the phenomena that occur in certain populations. The research sample was 40 respondents who were taken based on inclusion criteria using a purposive sampling technique. The analysis used is univariate analysis and is presented in the form of a percentage. Results: the result is that the majority of those suffering from DM are 56-65 years old, 19 respondents (47.5%), female sex 30 respondents (75.0%), occupation IRT 17 respondents (42.5%), education last high school 21 respondents (52.5%), ethnic Malays 26 respondents (65.0%), long suffering from DM 6-10 years 20 respondents (50.0%), and diabetes oral medication consumed was Metformin by 26 respondents (65.0%) and dietary adherence using the DM-DOS application were 30 respondents (75.0%) Conclusion: Implementation and adherence to a diet based on the DM-DOS Application diet using the DM-DOS application is effective in managing a good diet for people with diabetes mellitus.